TikTok sebagai Media Ekspresi Sosial Budaya dan Kritik Sosial Mahasiswa UIN Syarif Hidayatullah Jakarta - Supia, Asnun; Putri, Esha Cinta Nayuana; Sulistiyaningtias, Intan; Wardhana, Rechal Azhari; Saefudin, Arif (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2025)
TikTok has developed into a digital platform that functions not only as a source of entertainment but also as a medium for socio-cultural expression and social critique among students at Syarif Hidayatullah State Islamic University (UIN) Jakarta. This study aims to examine how students use TikTok as a participatory space to convey ideas, values, and perspectives on social issues through creative content. A qualitative case study approach was employed, with data collected through in-depth interviews, content observation, and documentation of student creators actively producing videos on social, cultural, and critical themes. The findings reveal that TikTok serves as a platform for identity expression, reflective communication, and collaborative media, blending religious values, popular culture, and student intellectualism. Through short informative and satirical videos, students articulate their perspectives on campus issues, morality, and social realities in a creative and respectful manner. TikTok also promotes a new communication culture grounded in digital creativity, media literacy, and social engagement. Theoretically, this research contributes to the study of digital communication among Islamic students, while practically, it offers recommendations for universities to enhance digital literacy and media ethics in the contemporary technological era.